STRATEGI KOMUNIKASI PEMASARAN UMKM KULINER DALAM MEMANFAATKAN DIGITAL MARKETING UNTUK MEMPERTAHANKAN PEMASUKAN DI MASA PANDEMI COVID-19 - Ghania Sofia Sabila, (2021)
A marketing strategy based on a marketing mix is used to achieve this with the stages of the communication strategy, segmentation, targeting, and positioning, which are used as the basis for marketing planning. Market-oriented strategic planning is the managerial process of developing and keeping the organization's objectives, skills and resources in line with changing market opportunities. Marketing strategy focuses on the company's long-term goals and involves planning marketing programs to realize the company's goals. Companies rely on marketing strategies to launch their product or service lines, including new products and services. Marketing strategy is the process of planning and implementing company policies to realize the company's goals in accordance with the company's vision. The purpose of this study was to determine the Marketing Communication Strategy of Culinary SMEs in Utilizing Digital Marketing to Maintain Income During the Covid-19 Pandemic. This research was conducted in South Tangerang City, researchers chose several areas in the Benda Baru, Pamulang Permai and East Ciputat areas. This type of research is descriptive qualitative. Data collection is done by conducting observations, interviews and documentation. Researchers conducted research using purposive sampling technique to collect informants. This type of research uses a descriptive qualitative type to explain the phenomenon in depth through data collection and the priority is a problem that is included in the quality of the data. The data collection technique of this research used primary data and secondary data. In the selection and determination of key informants and informants, researchers have categories that are in accordance with those that have been determined by using data analysis techniques, data reduction, data presentation and drawing conclusions on the data. The location in this study was chosen in South Tangerang City which has been categorized as culinary MSMEs that managed to occupy the first and second positions out of 7 sub-districts in South Tangerang City. This study shows several results that the application of a communication strategy with the SOSTAC model provides the point in this model that several MSMEs have their own advantages that are run by MSMEs to maintain their income during the Covid-19 pandemic by utilizing various social media, transport media and also applications. specially created by MSMEs in order to provide developments for their companies to maintain sales. Social media Instagram is one of the media to promote Culinary MSME products in South Tangerang City and provide product information to promote their sales. The internet is the key to sales during a pandemic situation that makes it impossible not to use social media.